INTERNATIONAL NEGOTIATIONS AS AN OBJECT OF METHODOLOGICAL ANALYSIS IN THE CONTEXT OF HYBRID WARS - Yeremieieva, Iryna; Marhulov, Artur (Current Problems of Sustainable Development, 2026)
The article examines the transformation of international negotiations in the context of contemporary hybrid wars. Classical theoretical approaches to the negotiation process and their limitations within modern conflicts are analyzed, particularly in situations where diplomatic mechanisms are integrated into broader strategies of political, informational, and security influence. The study substantiates the necessity of applying an interdisciplinary methodological approach combining the instruments of international negotiation theory, hybrid warfare studies, and the methodology of international relations research. A classification of state negotiation strategies in hybrid conflicts is proposed, and their impact on national and regional security is determined. Particular attention is paid to the analysis of negotiation practices in contemporary international conflicts and their role within the system of states’ strategic communications.